IMPLEMENTASI PENJUALAN OBAT HARGA ECERAN TERTINGGI (HET) DALAM RANGKA PERLINDUNGAN KONSUMEN OLEH PELAKU USAHA APOTEK DI KOTA PEKANBARU - Topan, Wisnu; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The pharmacy is a place to do pharmaceutical work and distribution of health supplies as well as one place for consumers to buy drugs, pharmacies are places that provide or sell drug needs for consumers to meet the needs of drug users. Business people or pharmacies are places where people sell drugs. Along with the development of the age, it is known that the term drug is a material or alloy of materials, including biological products that are used to influence or investigate the physiological system or pathological conditions in the framework of determining diagnosis, prevention, healing, recovery, improvement in health and contraception, for humans.The problem that the authors base on this research is how the implementation of drug sales on HET in the city of Pekanbaru and what efforts can be made by consumers towards the sale of drugs on HET in the Pekanbaru City area, while the purpose of this study is to find out whether the price of drugs has been in accordance with the Decree of the Minister of Health in the area of Pekanbaru City and to find out what efforts can be made by consumers on the sale of drugs on HET at pharmacies in the city of Pekanbaru.This type of research is classified into empirical or sociological research, because in this study the author directly conducts research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at a pharmacy in the city of Pekanbaru and Pekanbaru City Health Office and BPOM Pekanbaru City, the data sources used were: primary data and secondary data, data collection techniques in this study by observation, interviews and literature review.The results of this study are that the drug price determination by the government is based on allegations of cartel indications in drug sales, so the Business Acting Competition Commission (KPPU) urged the government to set the highest retail price on drugs, and KEPMENKES No. 2006 was issued. 069 / Menkes / SK / II / 2006 concerning the Inclusion of the Highest Retail Price (HET) in number 3 "That the public needs to get information about the Highest Retail Price (HET) from the drugs they consume in learning and consumer protection efforts," which have now been updated with KEPMENKES RI Number 98 of 2015, in fact there are still many business people who sell drugs on HET, this violates the provisions of Law Number 8 of 1999 concerning Consumer Protection, which are written in Article 60 to Article 63 can be in the form of administrative sanctions and sanctions principal crimes, as well as additional forms of seizure of certain goods, announcement of judges' decisions, compensation payments, orders to terminate certain activities that cause consumer losses, obligations to withdraw goods from circulation, or revocation of business licenses.Keywords: Pharmacy, Business Actor, HET Drug.